Artificial reproduction of pacific salmons in the Amur River basin: history, current state, prospects - D. V. Kotsyuk (Известия ТИНРО)
Experience of pacific salmon artificial reproduction is discussed. Generalized data on juveniles (mostly fall chum salmon) release from hatcheries in the Amur River basin are presented. Information about the fish eggs origin (collection points) and transportation to incubation is provided. Some local features of salmon hatcheries are noted. Thus, the hatcheries in the middle Amur (Teplovsky and Bijansky) used previously the eggs collected in local tributaries of the Amur but recently, in conditions of low abundance of spawners, they transfer the eggs for incubation from fish farms located in the lower Amur. On the contrary, the hatcheries in the lower Amur (Udinsky, Gursky, and Anyuisky) collected the eggs in many dispersed sites in the beginning of their exploitation, but later, when local herds of artificial origin had appeared, they collected the eggs from producers coming to the hatcheries. This experience of eggs collection in dispersed temporary sites could be useful for periods of low stocks of pacific salmons in the Amur basin. The last such period started in 2017, so the fishery officials, as the Amur branch of Glavrybvod, can use this approach. Large transfers of chum eggs within the basin and from other rivers of the Okhotsk Sea and Japan Sea basins, presumably could affect genetic diversity, population structure and gene pool of this species. First results on evaluation efficiency of salmon hatcheries are discussed on the data of otolith marking started in 2015. Negative dependence of chum salmon catch on release of their juveniles is found: increasing of the juveniles output does not provide higher catches. Besides, the number of producers returned to hatcheries does not depend on the number of juveniles released from these hatcheries in the past, but corresponds with general dynamics of salmon stocks in the entire Amur basin. We believe that returns of chum salmon of wild and artificial origin have similar changes caused by same factors influencing on fish in the river and marine periods of their life.